Development of a Protocol to Couple Wave and CFD Solvers Towards Reproducible CFD Modeling Practices for Offshore Applications - Bouscasse, Benjamin; Ducrozet, Guillaume; Kim, Jang Whan; Lim, Hojoon; Choi, Young Myung; Bockman, Arne; Pakozdi, Csaba; Croonenborghs, Eloïse; Bihs, Hans (Volume 1: Offshore Technology, 2020)
International audience Generating waves inside the CFD domain is a topic of interest in the offshore and naval industry. For practical reasons it is useful to use a potential wave kinematic solver (PWKS) to generate incident waves and use this solution to initialize and propagate incident waves in the CFD solver. Protocols to transfer the wave data from PWKS to CFD solver have been developed to ensure the reproduction of the wave kinematics from a PWKS in CFD solvers. Based on the survey results from a number of PWKS and CFD solvers available, the paper presents the various ways to express the solution and what is needed to reconstruct the fields needed in the CFD.